(3OjhGf GdTQja GdQVis - (3eMeO Hf GdMSjf Hf ehSi GdYdhj GdMSjfj GdehShj, GdTQja GdQVj , CHh GdMSf,J (B406 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf GdQVi jeOM GdWGFY ddg CejQ GdeDefjf gi SdhI PgHJ Hcd eQGe hGdMH fgH JWGhd GdCjGe s
(3BNQgG (B:s
(3fGO HGdQcH bO HdZJ Edi GdHMQ aZQS Hg caGc caGc s
(3GdfUa GdChd efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B261s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdCOHs